Reposisi Manajemen dalam Menjawab Problema Sekolah Swasta Islam dari Biaya Pendidikan Hingga Pelaksanaan Kurikulum Sekolah - Elva Novianty; Hendra Harmi; Ifnaldi Ifnaldi; Dina Hajja Ristianti (An-Nahdloh: Journal of Education and Islamic Studies, 2025)
This study aims to shed light on how Sekolah Dasa Unggulan Aisyiyah Taman Harapan Curup (SDUA THC), a leading Islamic elementary school, is repositioning its management approach to address the real challenges faced by Islamic private schools, especially in managing educational costs and implementing the Merdeka Curriculum. Using a descriptive qualitative method and a case study approach, data were gathered through in-depth interviews with the school principal, observations of school activities, the school action plan, the school financial documents, and an analysis of curriculum-related documents. The results show that SDUA THC has taken meaningful steps to reshape its management in ways that align with both the needs of the school and the values of Islamic education. These steps include focusing on improving the quality of learning through Islamic values, managing finances fairly and transparently, integrating technology into daily teaching practices, continuously supporting teachers’ professional growth, applying the curriculum flexibly with Islamic principles at its core, and building stronger partnerships with both the government and the local community. The study concludes that the school’s efforts are grounded in deep Islamic values — ihsan (striving for excellence), itqan (working with care and professionalism), maslahah (seeking the common good), and ta’awun (helping one another through collaboration). These values not only guide the school’s management but also inspire a more just, holistic, and meaningful educational experience for all. Keywords: Islamic Education Management, Problems of Islamic Private Schools, Cost of Education, Merdeka Curriculum